Meeting rising expectations of hopes for peace in post peace accord Northern Ireland - Kawser, Ahmed (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2012)
The Good Friday Agreement (GFA) formally brought about the cessation of open political violence and a semblance of normalcy returned to Northern Ireland. Over the years varied peacebuilding efforts were undertaken both by external and internal actors in Northern Ireland and the Border Area to support the peace process. This study explores the impact of peacebuilding and reconciliation in Northern Ireland and the Border Counties based on interviews with funding agency community development officers, and NGO civil society leaders engaged in the overall peace process. The participants narratives indicate how the GFA has contributed towards de-escalating violence, reducing sectarianism, fostering cooperation between macro political level efforts and micro grassroots level peacebuilding initiatives by creating an institutional framework for cross-community cooperation.
Keywords: Severna Irska; mirovni procesi; Velikonočni mirovni sporazum; ekonomska pomoč; mirovni sporazumi